The Affective Processes of Ethical Leadership: The Role of Moral Emotions - Jeong, Sophia Soyoung; Sun, Cong (Timothy); Yam, Kai Chi (Journal of business ethics, 2025)
Building on appraisal theory of emotions and theories on moral emotions, we contend that ethical leadership triggers other-praising moral emotions directed at the supervisor and leads to feedback-seeking behavior. We further predict that the affective processes of ethical leadership have implications for workplace behaviors, namely organizational citizenship behavior directed at the supervisor and employee voice. We develop a new measure of supervisor-directed, other-praising moral emotions and test the validity of the measure. Then, we test and find support for the proposed hypotheses using a sample of 231 full-time employees in China with a time-lagged survey design and structural equation modeling. Theoretical and practical implications for ethical leadership and moral emotions are discussed.